High-strength and high-damping ZA22 / 6061 layered composite material and preparation method thereof

By using a five-layer symmetrical ZA22/6061 layered composite material and a specific heat treatment process, the interfacial bonding problem of ZA22/6061 composite material was solved, achieving a breakthrough in comprehensive performance with high strength, high damping, and low density, with performance significantly superior to existing technologies.

CN121340706APending Publication Date: 2026-01-16HEBEI UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511913104.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-18
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing technologies struggle to successfully prepare high-strength, high-damping, and low-density ZA22/6061 layered composite materials through hot rolling processes, due to challenges in interfacial bonding, narrow process windows, and difficulties in synergistic microstructure control.

Method used

The ZA22/6061 layered composite material with a five-layer symmetrical structure, through a solution treatment and aging heat treatment process, combined with a specific rolling procedure and synergistic heat treatment, forms an interface layer of suitable thickness, which solves the problems of mismatch in physical properties and incompatibility of heat treatment regimes between ZA22 and 6061 alloys.

Benefits of technology

It achieves an excellent balance of high strength, high plasticity, and high damping in the material, with a yield strength ≥180 MPa, tensile strength ≥190 MPa, elongation ≥20%, and room temperature internal friction value not less than 0.028. Its performance is significantly better than that of single materials and melt infiltration process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121340706A_ABST
    Figure CN121340706A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength and high-damping ZA22 / 6061 layered composite material and a preparation method thereof. The composite material is of a five-layer sandwich structure formed by sequentially and symmetrically overlapping an outer layer, a middle layer, a central layer, a middle layer and an outer layer, in the preparation method, through the solid solution and aging heat treatment process, the optimization requirements of the microstructures of the two alloys can be met at the same time; and meanwhile, an interface layer which consists of fine grains and is proper in thickness is formed in situ at the interlayer interface. The inherent problem that two alloy heat treatment systems are incompatible is successfully solved, the yield strength of the obtained material is larger than or equal to 180 MPa, the tensile strength is larger than or equal to 190 MPa, the ductility is larger than or equal to 20%, and meanwhile the room-temperature internal friction value of the material at the testing frequency of 0.5 Hz is not lower than 0.028.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal layered composite material preparation technology, specifically to a high-strength, high-damping ZA22 / 6061 layered composite material and its preparation method. The composite material is characterized by having a five-layer symmetrical structure and being prepared by the following hot rolling process, exhibiting excellent comprehensive properties of high strength, high damping, and low density. Background Technology

[0002] Zinc-aluminum eutectoid alloys (Zn-22Al (wt%), i.e., ZA22 alloy) are an important class of damping materials, widely used in aerospace precision instruments, transportation, and automotive industries due to their excellent damping and vibration reduction performance, good casting properties, wear resistance, and corrosion resistance. However, while possessing high damping characteristics, this alloy also has significant drawbacks such as relatively low strength and relatively high density. This contradiction severely restricts its application in high-end equipment, especially in load-bearing structural components with stringent requirements for lightweighting and high specific strength (such as high-performance engine parts, aerospace load-bearing structures, and precision instrument supports). On the other hand, 6-series aluminum alloys (such as 6061 aluminum alloy), as typical wrought aluminum alloys, have a series of advantages such as low density, high specific strength, and good formability, making them one of the ideal materials for lightweight structures. However, the damping performance of this type of aluminum alloy is generally poor, and it cannot effectively suppress vibration and noise.

[0003] From a materials design perspective, if the high-damping ZA22 alloy can be successfully combined with the high-specific-strength 6061 aluminum alloy to prepare a layered composite material, it is expected that the advantages of both materials can be complemented to obtain an "ideal" new functional structure integrated material with high strength, high damping, and low density, thus meeting the growing demand of modern industry for comprehensive material performance. This concept has enormous theoretical application potential and market prospects. Reported preparation processes for ZA22 / Al and ZA22 / 6061 composite materials all require first preparing porous aluminum foam or foamed 6061 alloy through a molten metal infiltration method, followed by pouring ZA22 alloy melt into the foam pores, and finally obtaining the final material after cooling. However, this method suffers from problems such as cumbersome process steps, limited size of the prepared composite material, and difficulty in completely avoiding casting defects.

[0004] Among the many metal composite technologies (such as explosive composite method, diffusion welding method, etc.), hot rolling composite method is regarded as one of the most promising process routes due to its low process cost, high production efficiency and easy large-scale production. However, the composite of ZA22 alloy and 6061 aluminum alloy by hot rolling process faces severe challenges in actual technology. The core difficulties are: (1) Mismatch of physical properties: ZA22 alloy and 6061 aluminum alloy have significant differences in basic physical properties such as melting point, elastic modulus, and coefficient of thermal expansion. This difference leads to inconsistent deformation behavior during hot rolling composite process, large interface bonding stress, and difficulty in forming a strong and dense metallurgical bond. (2) Narrow process window: If the rolling temperature, reduction amount, pass interval and other parameters are not properly controlled, defects such as pores and cracks are easily generated at the bonding interface, which directly become the weak points of the composite material structure, resulting in mechanical properties far below theoretical expectations. (3) Difficulty in synergistic control of microstructure: ZA22 and 6061 each have different optimal heat treatment regimes. Conventional heat treatment processes struggle to simultaneously optimize both the composite interface and the microstructure of each phase. Improper process design may fail to induce synergistic effects such as interface strengthening, grain refinement, and precipitation strengthening, potentially leading to a trade-off between strength and damping performance, thus preventing the achievement of the desired "1+1>2" composite objective.

[0005] Therefore, although ZA22 / 6061 composite materials have a promising theoretical future, overcoming the interfacial bonding challenges through a stable and reliable specialized preparation process, and synergistically controlling the microstructure to achieve a balance between high strength, high damping, and low density, has long been a technical bottleneck that those skilled in the art have sought to solve but have yet to fully overcome. Currently, there is a lack of mature solutions that can effectively address these problems and successfully prepare high-performance ZA22 / 6061 layered composite materials. Summary of the Invention

[0006] The technical problem to be solved by this invention is to overcome the shortcomings of the prior art and provide a high-strength, high-damping ZA22 / 6061 layered composite material and its preparation method. This composite material is a five-layered, symmetrical structure composed of alternating ZA22 and 6061 alloys. In the preparation method, a solution treatment + aging heat treatment process can simultaneously meet the optimization requirements of the microstructure of both alloys; simultaneously, an interface layer of suitable thickness composed of fine grains is formed in situ at the interlayer interface. This invention successfully solves the inherent problem of incompatibility between the heat treatment regimes of the two alloys, resulting in a material with a yield strength ≥180 MPa, tensile strength ≥190 MPa, elongation ≥20%, and a room temperature internal friction value of not less than 0.028 at a test frequency of 0.5 Hz.

[0007] The technical solution of this invention is: A high-strength, high-damping ZA22 / 6061 layered composite material, which is a five-layer "sandwich" structure composed of an outer layer, an intermediate layer, a central layer, an intermediate layer, and an outer layer stacked symmetrically in sequence; The central layer and outer layer are both made of ZA22 alloy, and the intermediate layer is made of 6061 aluminum alloy. The overall thickness of the composite material is 2–3 mm, the thickness of each ZA22 alloy layer is 550–850 μm, and the thickness of each 6061 aluminum alloy layer is 100–275 μm.

[0008] The preparation method of the high-strength, high-damping ZA22 / 6061 layered composite material includes the following steps: Step 1: Raw material preparation Prepare ZA22 alloy sheet and 6061 aluminum alloy sheet; The thickness of ZA22 alloy plate is 3.8–5.2 mm, and the thickness of 6061 alloy plate is 0.7–1.7 mm. The second step is pre-treatment before rolling. After cleaning, ZA22 alloy plate and 6061 aluminum alloy plate are heated separately for homogenization treatment, and then cooled in the furnace. Among them, ZA22 alloy plate is kept at 370-390℃ for 0.5-1.5h; 6061 aluminum alloy plate is kept at 540-560℃ for 4.5-5.5h. The third step is surface treatment and blank assembly. The surfaces of the two alloy plates after processing are polished separately. Five layers of billets are symmetrically stacked in the order of "ZA22 alloy plate / 6061 aluminum alloy plate / ZA22 alloy plate / 6061 aluminum alloy plate / ZA22 alloy plate", with a total thickness of 12-19 mm. After mechanical fixing, they are put into a vacuum sleeve and sealed to obtain a sleeved billet; the final rolling thickness is 2-3 mm. The alloy plate is polished by using an angle grinder and sandpaper in sequence.

[0009] Step 4, hot rolling composite After preheating the cladding billet to 395–405℃, it is subjected to multi-pass hot rolling (single-pass reduction of 15–25%, total reduction ≥83.3%). After every two rolling passes, it is returned to the furnace and held at 395–405℃ for 10–15 min; after rolling, it is water-cooled, and after the cladding is removed, ZA22 / 6061 layered composite billet is obtained. Step 5, heat treatment The ZA22 / 6061 layered composite preform obtained in the previous step was solution treated at 360℃~400℃ for 0.8~1.2h, and then artificially aged at 175~185℃ for 0.8~1.2h, followed by air cooling to obtain the ZA22 / 6061 layered composite material.

[0010] The beneficial effects of this invention are as follows: The comprehensive performance of the material has been significantly improved, achieving an excellent unity of high strength, high plasticity, and high damping. This invention abandons the complex process of "preparing a porous skeleton + melt pouring" in the early stage, and successfully prepares a five-layer symmetrical layered composite material of ZA22 / 6061 for the first time through innovative hot rolling composite and synergistic heat treatment process. This material achieves synergistic performance gains that are difficult to achieve with a single alloy or conventional composite method: (1) Compared with a single material: As shown in the examples, the yield strength of the obtained material is up to 248 MPa (as shown in sample #4 of Example 3), the elongation after fracture is up to 31% (as shown in sample #3 of Example 2), and the room temperature internal friction value is up to 0.0556 (as shown in sample #3 of Example 2). Its strength and plasticity are several times that of a single ZA22 alloy with high damping (comparative example #1, yield strength 111 MPa, elongation 3%), while its damping performance significantly surpasses that of a single 6061 aluminum alloy with high strength (its typical internal friction value is usually less than 0.01). (2) Compared with the closest existing technology (melt infiltration method): The material of the present invention completely eliminates the defects such as porosity and shrinkage that are difficult to avoid in the casting process of the melt infiltration method, thereby obtaining a dense and tough metallurgical bonding interface. This is directly reflected in the qualitative leap in mechanical properties: the elongation rate (≥20%) of the material of the present invention is much higher than that of the usually brittle casting composite material, achieving both high strength and high plasticity, which is difficult to achieve in the melt infiltration process.

[0011] 2. The process innovation is not obvious, and the combination of key parameters has solved the inherent technical problem. The core creativity of this invention lies in the discovery and verification of the decisive role of the whole set of process parameters: "specific rolling process (400℃, ≥83.3% reduction, heat preservation between passes) + specific synergistic heat treatment (solution at 360℃~400℃ + aging at 180℃)". (1) Solving inherent contradictions: This combination is not a simple patchwork of conventional processes, but is designed specifically to solve the long-standing technical problem of mismatch between the physical properties of ZA22 and 6061 alloys and incompatibility of heat treatment windows. Examples have shown that this combination can unexpectedly form a fine-grained transition layer of suitable thickness in situ at the heterogeneous interface, which is fundamentally different from traditional methods such as melt infiltration that rely on melt solidification to form an excessively wide and brittle phase interface. (2) Synergistic strengthening: This unique interface structure, together with the synergistic regulation of the two-phase matrix structure by the process (refinement of the ZA22 layer eutectoid structure and strengthening of the 6061 layer precipitates), jointly induces a multi-faceted synergistic effect of "interface toughening, grain refinement, and precipitation strengthening". This is the fundamental mechanism by which the material of this invention can break through performance bottlenecks and achieve a "1+1>2" effect, which cannot be foreseen by those skilled in the art based solely on conventional knowledge.

[0012] 3. Possesses excellent performance designability and process controllability, with clear prospects for industrial application. This invention can achieve targeted control of the final performance combination of materials by adjusting the solution temperature (360℃, 380℃, 400℃), providing flexible solutions to meet different application needs: (1) Pursuing ultimate strength: Using 400℃ solution (as in Example 3), the highest strength (yield strength 248 MPa) can be obtained, suitable for high load-bearing components. (2) Pursuing optimal comprehensive performance: Using 380℃ solution (as in Example 2), while maintaining high strength (yield strength 192 MPa) and high plasticity (elongation 31%), the high damping performance (internal friction 0.0556) can be retained to the maximum extent, achieving the optimal balance. (3) Pursuing high damping and good plasticity: Using 360℃ solution (as in Example 1), excellent plasticity (elongation 29%) and qualified damping can be obtained, while the strength is significantly higher than that of the matrix.

[0013] This characteristic of being able to "customize" material properties by adjusting a single process parameter makes the production process of this invention highly controllable and repeatable, laying a solid foundation for large-scale industrial application.

[0014] In summary, this invention not only achieves innovation in the material system, but more importantly, it successfully overcomes long-standing technical obstacles through a set of non-obvious specialized processes, producing high-performance layered composite materials with comprehensive performance significantly superior to the closest existing technologies, and possessing good designability. The technological progress is outstanding and the application value is significant. Attached Figure Description

[0015] Figure 1 The yield strength, tensile strength, and elongation of different samples; Figure 2 The room temperature damping performance of different samples; Figure 3 The image shows the microstructure of sample #3 obtained in Example 2, where (a) is a distribution diagram of the ZA22 alloy layer and the 6061 alloy layer in the ZA22 / 6061 layered composite material; and (b) is a phase distribution diagram in the ZA22 / 6061 layered composite material. Detailed Implementation

[0016] Example 1: The first step is to prepare ZA22 and 6061 raw materials. Accurately weigh high-purity zinc (purity ≥99.9wt%) and high-purity aluminum (purity ≥99.9wt%) according to the nominal composition ratio of ZA22 alloy, melt, stir, and cast into ingots at 700℃. 6061 aluminum alloy is a commercially available sheet material.

[0017] The second step is pre-treatment before rolling. The obtained alloy wire is cut into samples with dimensions of 40mm×70mm×4mm (ZA22) and 40mm×70mm×1.5mm (6061). After ultrasonic cleaning with anhydrous ethanol and drying, homogenization treatment is performed: ZA22 is held at 380℃ for 1 hour, and 6061 is held at 550℃ for 5 hours, followed by furnace cooling.

[0018] The third step is surface pretreatment and stacking fixation. Use an angle grinder and sandpaper to grind the alloy surface until it is uniformly rough. Then, stack five layers symmetrically in the order of "ZA22 / 6061 / ZA22", with a total thickness of 15 mm. Drill holes at the four corners of the stack and fix them with rivets. Finally, put the entire blank into a vacuum sleeve and seal it.

[0019] The fourth step is hot rolling. After preheating the cladding billet to 400℃, it is immediately hot rolled. The reduction per pass is 20%, and 8 passes are rolled, with a total reduction of not less than 83.3%, and a final rolled thickness of approximately 2.5 mm. After every 2 passes, the sample is returned to the furnace and held at 400℃ for 10 minutes, and then water-cooled after final rolling.

[0020] Step 5, heat treatment. The rolled composite material was subjected to solution treatment (360℃ / 1h) and artificial aging treatment (180℃ / 1h), followed by air cooling, and the resulting sample was designated as #2.

[0021] The test results of yield strength, tensile strength, elongation, and room temperature damping performance of sample #2 obtained in this embodiment are shown below. Figure 1 and Figure 2Mechanical properties were measured using an INSTRON universal testing machine at room temperature with a constant tensile rate of 1 mm / min. Damping properties were determined using a dynamic thermomechanical analyzer (DMA, Q800) at a test frequency of 0.5 Hz, measuring the internal friction value. Test results showed that sample #2 had a yield strength of 183 MPa, a tensile strength of 193 MPa, an elongation of 29%, and a damping value (internal friction value) of 0.0286. Compared to the comparative single ZA22 alloy (sample #1, yield strength 111 MPa, tensile strength 117 MPa, elongation 3%, internal friction value 0.0681), sample #2 showed improvements in yield strength, tensile strength, and elongation of approximately 65%, 65%, and 867%, respectively. Although the damping performance decreased slightly, a synergistic improvement in strength and plasticity was achieved, resulting in a fundamental improvement in overall performance. It should be noted that although the damping value of the composite material in this example is lower than that of the original ZA22 alloy, its value (0.0286) is still within the recognized high damping performance range, which is sufficient to support its application as a damping material. In essence, it is still a "high damping" material.

[0022] Unless otherwise specified, the performance tests in the following embodiments all adopt the methods described in this embodiment.

[0023] Example 2: The first step is to prepare ZA22 and 6061 raw materials. Accurately weigh high-purity zinc (purity ≥99.9wt%) and high-purity aluminum (purity ≥99.9wt%) according to the nominal composition ratio of ZA22 alloy, melt, stir, and cast into ingots at 700℃. 6061 aluminum alloy is a commercially available sheet material.

[0024] The second step is pre-treatment before rolling. The obtained alloy wire is cut into samples with dimensions of 40 mm × 70 mm × 4 mm (ZA22) and 40 mm × 70 mm × 1.5 mm (6061). After ultrasonic cleaning with anhydrous ethanol and drying, homogenization treatment is performed: ZA22 is held at 380℃ for 1 hour, and 6061 is held at 550℃ for 5 hours, followed by furnace cooling.

[0025] The third step is surface pretreatment and stacking fixation. Use an angle grinder and sandpaper to grind the alloy surface until it is uniformly rough. Then, stack five layers symmetrically in the order of "ZA22 / 6061 / ZA22", with a total thickness of 15 mm. Drill holes at the four corners of the stack and fix them with rivets. Finally, put the entire blank into a vacuum sleeve and seal it.

[0026] The fourth step is hot rolling. After preheating the cladding billet to 400℃, it is immediately hot rolled. The reduction per pass is 20%, and 8 passes are rolled, with a total reduction of not less than 83.3% and a final rolled thickness of approximately 2.5 mm. After every 2 passes, the sample is returned to the furnace and held at 400℃ for 12 minutes, followed by water cooling after final rolling.

[0027] Step 5, heat treatment. The rolled composite material was subjected to solution treatment (380℃ / 1h) and artificial aging treatment (180℃ / 1h), followed by air cooling, and the resulting sample was designated as #3.

[0028] The yield strength, tensile strength, elongation, and room temperature damping performance of sample #3 obtained in this embodiment are shown in [reference needed]. Figure 1 and Figure 2 Its yield strength is 192 MPa, tensile strength is 202 MPa, elongation is 31%, and damping performance (based on internal friction value at a test frequency of 0.5 Hz) is 0.0556. Compared with the comparative single ZA22 alloy (sample 1, yield strength 111 MPa, tensile strength 117 MPa, elongation 3%, internal friction value 0.0681), sample 3 shows an increase in yield strength, tensile strength, and elongation of approximately 73%, 73%, and 933%, respectively. More importantly, at this solution treatment temperature, the material achieves extremely high strength and ductility while exhibiting a relatively small decrease in damping performance (only 22%), demonstrating the best overall performance balance.

[0029] The microstructure of sample #3 in this embodiment is as follows: Figure 3 As shown. According to Figure 3 The measurement results in (a) show that the thicknesses of the ZA22 alloy layers from top to bottom in the composite material are approximately 678 μm, 634 μm, and 708 μm, respectively; and the thicknesses of the 6061 alloy layers are approximately 244 μm and 236 μm, respectively. Additionally, from... Figure 3 As can be seen in (a), an interface layer is formed between the ZA22 alloy layer and the 6061 alloy layer, which further... Figure 3As shown in (b), the interface layer is an in-situ formed fine-grained transition layer of suitable thickness. This in-situ formed fine-grained transition layer is achieved through the core process of this invention—"precisely controlled hot rolling composite and synergistic heat treatment." Specifically, during the hot rolling process at 395–405℃ preheating and a single-pass reduction of 20% and a total reduction of ≥83.3%, the ZA22 and 6061 interfaces undergo intense atomic interdiffusion and dynamic recrystallization under the combined action of high temperature and large plastic strain. Subsequently, during the inter-pass heat treatment (395–405℃ / 10–15 min) and rapid water cooling after final rolling, the interface region inhibits grain growth and long-range element diffusion due to quenching, thereby "freezing" the high defect density and fine-grained rudimentary structure formed by hot rolling, laying the foundation for the microstructure evolution in subsequent heat treatment. Finally, a specially designed solution treatment (360–400℃ / 1h) provides sufficient temperature and time conditions for the interface region while simultaneously controlling the microstructure of the two-phase matrix. Through solid-state diffusion and phase transformation, the composition at this location is further homogenized, and the grains grow and stabilize appropriately, thus forming an in-situ transition layer with a gentle compositional gradient, fine grains, suitable thickness, and strong bonding. This process is completely different from traditional methods such as melt infiltration, which rely on melt solidification to form interfaces. It is a unique microstructure product obtained by this process through the synergistic effect of multiple stages of "strain-diffusion-quenching-solid-state phase transformation" in the solid state.

[0030] This in-situ formed fine-grained transition layer makes a significant contribution to achieving a synergistic improvement in the material's high strength, high plasticity, and high damping. First, as a gradient buffer between the ZA22 and 6061 phases, its fine-grained structure and high-density grain boundaries effectively relax the interfacial stress caused by the mismatch in physical properties, suppressing crack initiation and ensuring the material's high plasticity. Second, this layer achieves a strong metallurgical bond and becomes a bridge for efficient load transfer between the high-strength 6061 layer and the high-damping ZA22 layer, allowing the performance advantages of both to be synergistically utilized. Finally, this transition layer, together with the synchronous optimization of the matrix structure (such as ZA22 layer refinement and 6061 layer precipitation strengthening), constitutes a multi-faceted synergistic mechanism of "interfacial toughening, fine-grained strengthening, and precipitation strengthening," becoming the key microstructural foundation for breaking through performance bottlenecks and achieving comprehensive performance breakthroughs.

[0031] Example 3: The first step is to prepare ZA22 and 6061 raw materials. Accurately weigh high-purity zinc (purity ≥99.9wt%) and high-purity aluminum (purity ≥99.9wt%) according to the nominal composition ratio of ZA22 alloy, melt, stir, and cast into ingots at 700℃. 6061 aluminum alloy is a commercially available sheet material.

[0032] The second step is pre-treatment before rolling. The obtained alloy wire is cut into samples with dimensions of 40 mm × 70 mm × 4 mm (ZA22) and 40 mm × 70 mm × 1.5 mm (6061). After ultrasonic cleaning with anhydrous ethanol and drying, homogenization treatment is performed: ZA22 is held at 380℃ for 1 hour, and 6061 is held at 550℃ for 5 hours, followed by furnace cooling.

[0033] The third step is surface pretreatment and stacking fixation. Use an angle grinder and sandpaper to grind the alloy surface until it is uniformly rough. Then, stack five layers symmetrically in the order of "ZA22 / 6061 / ZA22", with a total thickness of 15 mm. Drill holes at the four corners of the stack and fix them with rivets. Finally, put the entire blank into a vacuum sleeve and seal it.

[0034] The fourth step is hot rolling. After preheating the cladding billet to 400℃, it is immediately hot rolled. The reduction per pass is 20%, and 8 passes are rolled, with a total reduction of not less than 83.3%, and a final rolled thickness of approximately 2.5 mm. After every 2 passes, the sample is returned to the furnace and held at 400℃ for 15 minutes, and then water-cooled after final rolling.

[0035] Step 5, heat treatment. The rolled composite material was subjected to solution treatment (400℃ / 1h) and artificial aging treatment (180℃ / 1h), followed by air cooling, and the resulting sample was designated as #4.

[0036] The yield strength, tensile strength, elongation, and room temperature damping performance of sample #4 obtained in this embodiment are shown in [reference needed]. Figure 1 and Figure 2 Its yield strength is 248 MPa, tensile strength is 257 MPa, elongation is 24%, and damping performance (based on internal friction value at a test frequency of 0.5 Hz) is 0.0351. Compared with the comparative single ZA22 alloy (sample 1#, yield strength 111 MPa, tensile strength 117 MPa, elongation 3%, internal friction value 0.0681), sample 4# shows an increase in yield strength, tensile strength, and elongation of approximately 123%, 120%, and 700%, respectively. This example demonstrates that the material reaches its peak strength at a solution treatment temperature of 400℃. Although the elongation and damping performance are adjusted compared to the sample (3#) treated at 380℃, the strength improvement is the most significant, providing a preferred solution for applications requiring ultimate strength.

[0037] Matters not covered in this invention are common knowledge.

Claims

1. A high strength high damping ZA22 / 6061 layered composite material, characterized in that, The composite material is a five-layer sandwich structure which is symmetrically stacked by outer layer, intermediate layer, center layer, intermediate layer and outer layer in turn; The material of the center layer and the outer layer is ZA22 alloy, and the material of the intermediate layer is 6061 aluminum alloy; The overall thickness of the composite material is 2-3 mm, the thickness of each ZA22 alloy layer is 550-850 μm, and the thickness of each 6061 aluminum alloy layer is 100-275 μm.

2. The preparation method of the high-strength, high-damping ZA22 / 6061 layered composite material as described in claim 1, characterized in that, The method comprises the following steps: First step, raw material preparation Prepare ZA22 alloy plate and 6061 aluminum alloy plate; The thickness of the ZA22 alloy plate is 3.8-5.2 mm, and the thickness of the 6061 alloy plate is 0.7-1.7 mm; Second step, pretreatment before rolling After the ZA22 alloy plate and the 6061 aluminum alloy plate are cleaned, they are respectively heated for homogenization treatment, and then cooled in the furnace; The ZA22 alloy plate is heated at 370-390℃ for 0.5-1.5h, and the 6061 aluminum alloy plate is heated at 540-560℃ for 4.5-5.5h; Third step, surface treatment and assembly The surfaces of the two treated alloy plates are respectively polished, and the five-layer blank is symmetrically stacked in the order of "ZA22 alloy plate / 6061 aluminum alloy plate / ZA22 alloy plate / 6061 aluminum alloy plate / ZA22 alloy plate", the total thickness is 12-19 mm, and the blank is mechanically fixed, then put into a vacuum bag and sealed to obtain a bagged blank; the final rolling thickness is 2-3 mm; Fourth step, hot rolling After the bagged blank is preheated at 395-405℃, it is subjected to multi-pass hot rolling; after every two passes, it is reheated at 395-405℃ for 10-15 min; after rolling, it is water-cooled, and after the bag is removed, a ZA22 / 6061 layered composite blank is obtained; In the hot rolling, the single-pass reduction is 15-25%, and the total reduction is ≥83.3%; Fifth step, heat treatment The ZA22 / 6061 layered composite blank obtained in the above step is subjected to solid solution treatment at 360-400℃ for 0.8-1.2h, and then artificial aging treatment at 175-185℃ for 0.8-1.2h, and then air cooling, to obtain a ZA22 / 6061 layered composite material.

3. The preparation method of the high-strength, high-damping ZA22 / 6061 layered composite material as described in claim 1, characterized in that, The polishing of the alloy plate is polishing with an angle grinder and sandpaper in turn.